Effect of free surface water level of Kenyir Dam on spillway structure using fluid-structure interaction (FSI) analysis - Radzi M.R.M.; Nashrudin M.N.; Zawawi M.H.; Abas A.; Azman A.; Hassani A. (American Institute of Physics Inc., 2023)
This paper investigated the effect of free surface water level of Kenyir Dam towards the stress and deformation of spillway structure by using fluid-structure interaction (FSI) simulation. The water flow across the spillway is visualized as modelled based on volume of fluid (VOF) scheme. For free surface water level of 155 m, higher stress is computed at the spillway (40.4 MPa) and at the downstream (8.9 MPa) compared to the result of free surface water level of 146 m. It is found that the higher the free surface water level caused high force exerted by the water flow on the spillway structure. 2019 Author(s).